A proposed classification of pseudoexfoliation syndrome (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To develop a classification of pseudoexfoliation syndrome (PEX) for use in cataract surgery on the basis of its features.Material and Methods: This study included 67 patients (67 eyes; age, 61 to 84 years) with PEX-associated cataract who underwent phacoemulsification with intraocular lens (IOL) implantation. Patients were divided into the following categories based on the features of surgical strategy: those that underwent standard phacovitrectomy without zonular protection; those that underwent phacoemulsification and no nucleus rotation during hydrodissection; those that required a capsular tension ring (CTR) implantation due to zonular weakness; and those that required suture IOL fixation.Results: The patient distribution based on the features of PEX and severity of the effect of PEX on the features of phacoemulsification cataract surgery allowed to determine the relationship of the surgical strategy with the maximum pupil dilation, severity of zonular weakness, increased lens mobility, and capacity of an IOL to maintain its correct position independently. Determining the relationship allowed us to systematize these features and develop a surgical classification of PEX. The classification scheme defines four stages of the syndrome; stage II is subdivided into two categories, category A and category B. Conclusion: The classification proposed was developed on the basis of the assessment of PEX in the above number of patients, and enabled systematizing the features of patients according to the features of the anterior segment of the eye. Moreover, the study is universal for the stages proposed. The classification can be used as a basis for further research on PEX.
Keywords: pseudoexfoliation syndrome; cataract; cataract associated with pseudoexfoliation syndrome; pseudoexfoliative glaucoma; phacoemulsification; intraocular lens position; intraocular lens fixation; pseudoexfoliation syndrome classification